2010
DOI: 10.1149/1.3473790
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Dendrite Formation in Li/Poly(ethylene oxide)–Lithium Bis(trifluoromethanesulfonyl)imide and N-Methyl-N-propylpiperidinium Bis(trifluoromethanesulfonyl)imide/Li Cells

Abstract: Lithium metal dendrite growth in Li/poly(ethylene oxide)–lithium bis(trifluoromethanesulfonyl)imide (PEOxLiTFSI) and in an ionic liquid, N -methyl- N -propylpiperidinium bis(trifluoromethanesulfonyl)imide (PP13TFSI) composite solid polymer electrolyte/Li was examined by direct in situ observation. Lithium dendrite formation was observed after 15 h of polarization at 0.5mAcm−2 and at 60°C on PEO18LiTFSI . The onset time was increased to 35 h at 0.5mAcm−2 by the addition of PP13TFSI into PEO18LiTFSI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 31 publications
6
126
0
Order By: Relevance
“…Liu et al 10 reported a similar relationship between the lithium dendrite onset time and the current density for a Li/PEO based electrolyte/Li cell at 60°C, where a composite polymer electrolyte of PEO 18 LiTFSI and PP13LiTFSI was used. The log R cc vs. log J curve showed good linearity in the range of 0.1 to 1.0 mA cm ¹1 with a slope of ¹1.25.…”
Section: ¹2mentioning
confidence: 73%
See 1 more Smart Citation
“…Liu et al 10 reported a similar relationship between the lithium dendrite onset time and the current density for a Li/PEO based electrolyte/Li cell at 60°C, where a composite polymer electrolyte of PEO 18 LiTFSI and PP13LiTFSI was used. The log R cc vs. log J curve showed good linearity in the range of 0.1 to 1.0 mA cm ¹1 with a slope of ¹1.25.…”
Section: ¹2mentioning
confidence: 73%
“…In the last 30 years, lithium dendrite formation on the lithium electrode from liquid electrolytes [4][5][6] and polymer electrolytes [7][8][9][10][11] has been widely studied. Lithium deposition on a lithium electrode from a conventional non-aqueous liquid electrolyte used for lithium-ion batteries resulted in lithium dendrite formation for a short period of polarization.…”
Section: Introductionmentioning
confidence: 99%
“…More attractive results were found for a composite of PEO 18 LiTFSI and a room temperature ionic liquid (RTIL) of N-methyl-N-propylpiperidinium-bis(trifluoromethanesulfonyl)imide (PP13TFSI). 22 The temperature dependence of the electrical conductivity for PEO 18 LiTFSI-xPP13TFSI is shown in Fig. 10.…”
Section: ¹2mentioning
confidence: 99%
“…We prepared a composite polymer electrolyte consisting of PEO 18 LiTFSI and PP13TFSI and examined the dendrite formation in Li/PEO 18 -LiTFSI-xPP13TFSI/Li using direct in situ observation at various current densities. 22 The relationship between lithium dendrite formation and the ionic transport properties of the composite polymer electrolyte is also discussed. 35 Matsumoto et al 36 reported that the LiTFSI ionic liquid in PP13TFSI enables the reversible plating-stripping of lithium metal.…”
Section: ¹2mentioning
confidence: 99%
See 1 more Smart Citation